Inflammatory bowel disease and cardiovascular disease: A two-sample Mendelian randomization analysis - Wu, Kaiwen; Li, Aoshuang; Liu, Lei; Shu, Tao; Xia, Demeng; Sun, Xiaobin (Frontiers in Cardiovascular Medicine, 2022)
Background: Although epidemiological studies have shown a positive relationship between inflammatory bowel disease (IBD) and risk of cardiovascular diseases (CVDs), a causal relationship has not been established. We conducted a two-sample Mendelian randomization (MR) study to explore the potential causal effect between IBD and CVDs. Methods: Summary statistics of single nucleotide polymorphisms on IBD and 14 CVDs were obtained from genome-wide association studies of European descent. The inverse-variance weighted (IVW) method was used as the main MR analysis, with complementary analyses of MR Egger, maximum likelihood, weighted median, penalized weighted media, simple mode and weighted mode methods. Multiple sensitivity analyses were used to evaluate the robustness of our results. Results: All P values were greater than 0.05 in the IVW method, showing no evidence of a causal association of circulating IBD with any CVD. Similar results were observed using other MR methods. No evidence of heterogeneity, pleiotropy, or outlier single-nucleotide polymorphisms was detected. Sensitivity analyses demonstrated the robustness of the results. Conclusion: The findings of this study provided no evidence to support that IBD has a large effect on risk of CVDs, which is in contrast to many previous observational reports. Further studies are needed to determine the potential mechanism of causality.